2004
DOI: 10.1089/104303404322886101
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Human Immunodeficiency Virus Hematopoietic Progenitor Cell-Delivered Ribozyme in a Phase I Study: Myeloid and Lymphoid Reconstitution in Human Immunodeficiency Virus Type-1–Infected Patients

Abstract: A phase I gene transfer clinical study was undertaken to examine the ability to introduce a potential anti-human immunodeficiency virus (HIV) gene therapeutic into hematopoietic progenitor cells (HPC), thereby contributing to multilineage engraftment. The potential therapeutic effect of genetically modifying HPC with protective genes in HIV-infected adults depends in part on the presence of adult thymic activity and myeloid capacity in the setting of HIV replication. Herein we report the presence and expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
103
0
1

Year Published

2006
2006
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 36 publications
0
103
0
1
Order By: Relevance
“…This result is unexpected under the assumption that the OZ1-transduced HSCs successfully engrafted, differentiated and expanded into the T-cell lineage, and maintained some level of anti-HIV protection over untreated CD4+ T cells. Similar Phase I trials-including reports from the same authors 4 -have confirmed successful engraftment, differentiation and expansion of autologous HSCs transduced with anti-HIV retroviral vectors. 2 Therefore, although the HSCs may have failed to engraft under the conditions of the trial, it is also possible that the anti-HIV ribozyme failed to protect the OZ1 cells from HIV-1 infection and replication.…”
mentioning
confidence: 59%
“…This result is unexpected under the assumption that the OZ1-transduced HSCs successfully engrafted, differentiated and expanded into the T-cell lineage, and maintained some level of anti-HIV protection over untreated CD4+ T cells. Similar Phase I trials-including reports from the same authors 4 -have confirmed successful engraftment, differentiation and expansion of autologous HSCs transduced with anti-HIV retroviral vectors. 2 Therefore, although the HSCs may have failed to engraft under the conditions of the trial, it is also possible that the anti-HIV ribozyme failed to protect the OZ1 cells from HIV-1 infection and replication.…”
mentioning
confidence: 59%
“…If these manipulated cells were intended to be used to therapeutically target the T lineage, our results suggest that they need only be differentiated as far as hematopoietic progenitor cells in vitro and that the thymus would then complete the differentiation program to CD4 ϩ and CD8 ϩ T cells in vivo. This type of approach might lead to improved therapeutic strategies to treat genetic hematopoietic disorders, such as X-linked SCID (19) or infectious diseases such as acquired immunodeficiency syndrome (20).…”
Section: Discussionmentioning
confidence: 99%
“…But in contrast to references 75 and 76, no selective advantage of the HIV-resistant CD4 + cells was observed. However, a companion study testing this vector in CD34 + cells did observe a selective survival advantage for CD4 + cells derived from CD34 + cells 78 .…”
Section: Early Genetic Antivirals In T Cellsmentioning
confidence: 99%
“…The results of clinical trials for HIV-1 using HS cells have been modest 14,78,119,120 . The numbers of peripheral blood cells containing the introduced gene have been low or undetectable in most subjects after the first few months, indicating low engraftment of genemodified HS cells.…”
Section: Hs Cell Therapiesmentioning
confidence: 99%